ENHANCES OF STRATEGY IMPROVEMENT OF SCHEDULED LION AIR COMPETITIVE TRANSPORTATION AIR SERVICES IN THE INDONESIAN BUSINESS COMPETITION. - Daniel D Rumani (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
Currently, Lion is in big trouble. This research aims to analyze the application competitive strategy of Low-Cost Carrier (LCC) taken by Lion in the business competition of scheduled commercial air transport services in Indonesia. Through measurement of market concentration: Concentration Ratio (CR), Index (HHI), and several equal sellers Lion have won the competition as the largest market shareholder since 2007 until now. Its success is because Lion can successfully cope with five competitive forces (Porter) : (1) buyer, (2) suppliers, (3) substitution, (4) newcomers, (5) rivalries, with LCC strategy. LCC can last long but not forever. The evolution of the value industry of the LCC strategy of excellence declined, pushing a heavy burden for Lion. Urgent need of strategy or another new business model, with strategic partners (domestic and foreign) to maintain and even improve company performance in the framework of Sustainable Competitive Advantage (SCA).